Simultaneous Kidney-Pancreas Transplantation With an Original "Transverse Pancreas" Technique: Initial 9 Years' Experience With 56 Cases - Paulino, J (2018)
An innovative technique for pancreas transplantation is described. The main aspect consists of the horizontal positioning of the pancreas, which allows a better venous outflow, thus preventing thrombosis and graft loss. The program of pancreas transplantation in this national reference center for pancreatic and liver surgery was started in 2007; the initial results were considered poor, resulting in the loss of half of the grafts due to venous thrombosis. After analyzing the possible causes, this technique was proposed and successfully implemented, reducing the postoperative complications, particularly the problem of venous thrombosis. A detailed description of the new surgical technique is provided. The main clinical and demographic characteristics of the 56 patients who underwent the surgery are analyzed. The incidence of venous thrombosis was 5.3% (3 patients) and graft loss was 3.5% (2 patients). Due to the good results, this technique became the standard surgery for transplantation of the pancreas in our center. The technique proved to be safe and successful. Due to the unique pancreas graft implantation, we called it "transverse pancreas surgery."